Thymoma and thymic carcinoma in children and adolescents: A report from the European Cooperative Study Group for Pediatric Rare Tumors (EXPeRT). Issue 16 (November 2015) - Stachowicz-Stencel, Teresa; Orbach, Daniel; Brecht, Ines; Schneider, Dominik; Bien, Ewa; Synakiewicz, Anna; Rod, Julien; Ferrari, Andrea; Cecchetto, Giovanni; Bisogno, Gianni
Abstract Background Thymomas and thymic carcinomas belong to a group of thymic epithelial tumours arising from the anterior mediastinum and, are extremely rare in children in which no therapeutic guidelines have been established. The aim is to describe paediatric characteristics of these tumours and give some therapeutic indications. Methods Retrospective analysis of clinical data and therapeutic characteristics of paediatric patients less than 18 years with thymic tumours treated between 2000 and 2012 registered in the European Cooperative Study Group for Pediatric Rare Tumors (EXPeRT) database of the cooperating national rare paediatric tumour working groups from France, Italy, Germany and Poland. Results Sixteen children with thymoma, median age 11 years and 20 patients with thymic carcinoma, median age 14 years were enrolled into study. At diagnosis complete primary resection was possible in 11 patients with thymoma and one with thymic carcinoma; resection with microscopic residue was performed in three cases and incomplete resection with macroscopic residue in four patients. Chemotherapy with various regimens was administered to 22 children; 17 of them as neoadjuvant chemotherapy. Eight patients with thymic carcinoma received additional radiotherapy. Seventeen children died (15 thymic carcinoma, two thymoma). Five-year overall survival for patients with thymic carcinoma is 21.0 ± 10.0%. Conclusions This study confirms the possibility to perform European retrospective analysis even in very rare paediatric tumours. Thymic carcinoma is associated with paediatric patients to give a very poor prognosis independently despite multimodal management. Multidisciplinary, multicenter approach and collaboration with adults' physician are necessary in order to propose homogenous guidelines.